2018
DOI: 10.3390/app8040597
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effects of Internal EGR by Variable Exhaust Valve Actuation with Post Injection on Auto-ignited Combustion and Emission Performance

Abstract: Variable valve mechanisms are usually applied to a gasoline combustion engine to improve its power performance by controlling the amount of intake air according to the operating load. These mechanisms offer one possibility of resolving the conflict of objectives between a further reduction of raw emissions and an improvement in fuel efficiency. In recent years, variable valve control systems have become extremely important in the diesel combustion engine. Importantly, it has been shown that there are several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The set goals could be achieved by applying modern technologies in order to optimize combustion and tribological processes [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The set goals could be achieved by applying modern technologies in order to optimize combustion and tribological processes [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the use of iEGR moderated combustion by delaying the ignition time, thus eliminating the oscillations of the in-cylinder pressure [120]. Cho et al [121] reported that the variable exhaust valve actuation with iEGR in diesel engines was beneficial for post-injection.…”
Section: Internal Exhaust Gas Recyclesmentioning
confidence: 99%
“…In addition, it has been stated that post-injection improves soot oxidation by increasing the probability of the fuel finding available oxygen. Cho et al [22] numerically studied the effect of iEGR application through recompression by reducing exhaust valve lift and duration and post-injection on emission and performance of a 4-cylinder direct injection diesel engine. Their findings showed that the iEGR by recompression is efficient in utilizing heat energy by increasing the EGR rate by about 10%.…”
Section: Introductionmentioning
confidence: 99%